Characterization of Some Ring Properties in Incidence Algebras - Esin, Songül; Kanuni Er, Müge; KOÇ, AYTEN (Taylor and Francis Online, 2011)
Let R be a ring with identity and I(X, R) be the incidence algebra of a locally finite partially ordered set X over R. In this article, we investigate the necessary and sufficient conditions for the incidence ring to be Ikeda-Nakayama, nil injective, NI, reduced, nonsingular and Kasch ring.
Keywords: Ikeda-Nakayama ring; Incidence algebra; Kasch ring; Nil-injective ring; Singular ideal